Online Social Network Analysis. - Fang, Binxing; Jia, Yan; Publishing House of Electronics Industry (Online Social Network Analysis ;, 2019)
The three volume set provides a systematic overview of theories and technique on social network analysis. Volume 1 of the set mainly focuses on the structure characteristics, the modeling, and the evolution mechanism of social network analysis. Techniques and approaches for virtual community detection are discussed in detail as well. It is an essential reference for scientist and professionals in computer science.